2017
DOI: 10.1038/s41598-017-14961-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of unusual peptides with new Cys frameworks in the venom of the cold-water sea anemone Cnidopus japonicus

Abstract: Sea anemones (Actiniaria) are intensely popular objects of study in venomics. Order Actiniaria includes more than 1,000 species, thus presenting almost unlimited opportunities for the discovery of novel biologically active molecules. The venoms of cold-water sea anemones are studied far less than the venoms of tropical sea anemones. In this work, we analysed the molecular venom composition of the cold-water sea anemone Cnidopus japonicus. Two sets of NGS data from two species revealed molecules belonging to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Actinoporin show consistent different hemolytic activity in all their representatives [11]. Sea anemones H. crispa is a pore-forming toxin belongs to actinoporins that show hemolytic activity [12]. Pocilopotoxin-Spi1 toxin (α-PCTX-Spi1) isolated from Stylophora pistillata shows hemolytic activity (table 1) [13].…”
Section: Hemolytic Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Actinoporin show consistent different hemolytic activity in all their representatives [11]. Sea anemones H. crispa is a pore-forming toxin belongs to actinoporins that show hemolytic activity [12]. Pocilopotoxin-Spi1 toxin (α-PCTX-Spi1) isolated from Stylophora pistillata shows hemolytic activity (table 1) [13].…”
Section: Hemolytic Activitymentioning
confidence: 98%
“…These successfully control angiogenesis and inhibit cell proliferation in vitro cancer cell cultures. These toxins displayed anticancer effects and inhibit the growth and proliferation of tumor and cancerous cells [1]. A number of toxins purified from anemones, centipedes, bees, or wasps, hornets, snails, spider and scorpion and sea, fish, toads, fry, and the snake has been isolated and screened for their anticancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the transcriptome sequencing of sea anemone venom and identification of venom-related peptides and proteins, which can be used for their structural and functional analyses and venom evolution in the fu-ture (Table 4, Ref. [18,46,87,109,135,136,[141][142][143]) [132,136]. Tentacles are ideal for transcriptomics analysis because the number and level of transcripts encoded by sea anemone peptide neurotoxins from tentacles are much greater than those encoded by sea anemone peptide neurotoxins from other tissues [132].…”
Section: Transcriptomics Technologymentioning
confidence: 99%
“…Sea anemone Urticinagrebelnyi contain Ugr 9-129 amino acid peptides cross-linked by two disulfide bridges shows analgesic activity [52] Ueq 12-1 is a unique peptide potentiator of the TRPA1 receptor. This is isolated from Urticinaeques that produces analgesic activity [53]. The cold-water sea anemone Cnidopus japonicas contain neurotoxins, toxin-like molecules, linear polypeptides (Cys-free), enzymes, which show analgesic effects [60] Sea anemone contains one bioactive peptide named α-AnmTxUeq 12-1 (Ueq 12-1) (fig.…”
Section: Analgesic Activitymentioning
confidence: 99%